Processamento e caracterização de nano-biocompósitos de Poli(hidroxibutirato-co-hidroxivalerato)/montimorilonita modificada organicamente (PHBV/OMMT) com adição de plastificante - Corrêa, Maria Clara Silveira (2010)
A current search for new materials that are economically viable and ecologically correct has led to the implementation of many studies aimed at improving the properties and processability of biodegradable polymers. This study sought to make viable the production of nano-biocomposites by conventional processing methods. It was selected a copolymer produced in Brazil from bacterial fermentation and completely biodegradable, poly(hydroxybutyrate-cohydroxyvalerate) PHBV, having an organo-modified montmorilonite (OMMT) as nanofiller, and acetyl tributyl citrate (ATBC) as plasticizer. The processing parameters and the formulations were controlled, yielding materials with good mechanical and barrier properties, having high biodegradability and better processability. The nano-biocomposites were characterized by thermal gravimetric analysis (TGA), differential scanning calorimetry (DSC), size exclusion chromatography (SEC), wide angle X-ray scattering (WAXS), transmission electron microscopy (TEM), X-ray photoelectron spectroscopy (XPS), tensile, impact, permeability, and biodegradability tests. The results indicate that the addition of a plasticizer improved the processability and the mechanical properties of the nano-biocomposites.